MUSLIM WOMEN AND THEIR EXPLOITATION IN NAME OF ISLAMIC TRADITIONS - Dr. Beena Dewan (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2022)
The Constitution of India has provided us with fundamental rights, duties and directive principles which focuses on many aspects including principle of gender equality which is exalted in the Preamble. Moreover, it has not only focused on granting equality to women in india but also empowers state to adopt measures to avoid discrimination against this gender. Article 14 talks about right to equality; Article 15 is about Prohibition of discrimination on groinds of religion, race, caste, sex, or place of birth, and article 15(3) specifically states: The State to make any special provision in favor of women and children. There are many more articles in Indian Constitution that talk about equality for women in every field despite that but still women in India are treated very differently. It seems that the law and especially the Constitution are not being taken very seriously in this patriarchal society. Despite the articles, reforms and campaigns for women empowerment we as a society has failed to provide equality to women of our country, they are still being subjected to violence, discrimination on basis of their gender, status and what not. There are many forms of torture that women are subjected to and one of them is in form of hardcore religious practices. Every religion has certain practices which they term as ‘sacred’ but where a woman is actually being exploited both physically and mentally. One such religion is Islam. Where the world is developing with a speedy pace in every field there are still many malpractices which are performed with women in the name of religion thereby causing mental and physical trauma. Women of Islam have no other choice but to adhere to those practices and not raise voice against the same. These so called rituals or practices hold no logic whatsoever. Despite of all the education and development women are subjected to cruelty in the name of religion.